PREFERENSI DAN PERSEPSI VISUAL ELEMEN FISIK KOTA PADA AREA TITIK NOL KOTA YOGYAKARTA - RA Laksmi Widyawati (Fakultas Teknik Universitas Borobudur, 2021)
The physical development of Yogyakarta City refers to the philosophy of itsformation, but tries to be adaptive to development. The imaginary axis lines of Yogyakartacity planning are strengthened and beautified, so that it can be appreciated and enjoyed byits citizens. The strengthening of this axis is done by improving the physical elementsaround the axis, maintaining kolonial buildings, strengthening pedestrians and open spacesas well as street furniture. The Zero Point Area, which is the final node of the Malioboropedestrian and bordering the Kraton area, is interesting to study because it has developedboth physical elements and supporting activities so that it becomes one of the choices forpublic spaces in Yogyakarta.This paper is the result of observations / studies of the visual perceptions of urbanresidents towards the physical elements of the city, and is complemented with theirfunctional preferences. These two things are expected to illustrate how city residentsappreciate their city. Before going to the field, I first conducted a visual perception of thephysical elements of the city by referring to the theory of visual perception, which is appliedto the physical elements of the city. During the pandemic, urban space is not optimallyfunctioning, but city residents who have lived in Yogyakarta for more than 2 years can stillappreciate it both in the form of memories before the pandemic and this pandemic period.Keywords: visual perception, preferences, physical elements of the city, zero point area